THE INFLUENCE OF ISLAMIC BRANDING HALAL CERTIFICATION AND GREEN MARKETING ON CONSUMER LOYALTY THROUGH PERCEIVED VALUE - Sugiharto, Totok; Santoso, Budi; Sanosra, Abadi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to examine the effect of islamic branding and green marketing on consumer loyalty with perceived value as an intervening. Method: This research is explanatory research. The population used in this research is MSME food and beverage consumers in Jember Regency using a non-probability sampling method. This research determined a sample of 1180 respondents. Data processing in this research uses Variance-based SEM or Partial Least Square (SEM-PLS) with the Warp-PLS 7.0 SEM PLS program. Results: Results of the research state that islamic branding and green marketing has significant effect on the perceived value. Islamic branding has insignificant effect on the consumer loyalty. Green marketing has significant effect on the consumer loyalty. Perceived value has significant effect on the consumer loyalty. Islamic branding and green marketing has significant effect on the consumer loyalty, mediated by perceived value. Novelty: This research tries to test a model related to marketing management by involving islamic branding and perceived value as intervening.